Reflections on Becoming an Applied Anthropologist - Preston, Richard J. "Dick" (Anthropologica, 2022)
In responding to the honour given me by this 2006 Weaver-Tremblay Award, I will sketch some aspects of my academic and non-academic background, ponder the label "applied," discuss the balance between intellectual inquiry and pragmatic anthropology, and give some examples of my applied work, focusing on the James Bay region.